Development of Pancasila monopoly learning media based on SAVI to improve Pancasila education learning outcomes - Bayu Adhi Dwi Yulianto; Susilo Tri Widodo (Research and Development in Education (RaDEn), 2024)
The low learning outcomes of students in interpreting the rules in the school and home environment need attention. This is caused by the teacher's teaching methods, which are less varied and interesting. This study aims to develop Pancasila monopoly media to improve PPKn learning outcomes. The study applies the 4D development model, which stands for Define, Design, Development, and Dissemination. This model was chosen because the stages of implementation are divided in detail and systematically. The analysis is descriptive of quantitative and qualitative data obtained through observation, interviews, and direct measurements in the field. The results of the media expert assessment obtained a score of 93.7% with very good criteria, and the material expert obtained a score of 96.2% with very decent criteria. Student learning outcomes increased to 82.32 from the previous score of 42.50. The increase was 39.8%. While the control class that did not use media increased its score from 49.05 to 75.48. The results of the N-Gain test obtained an average difference in the experimental class of 39.8 with an n-gain of 0.76 and a moderate criterion, and the effectiveness interpretation obtained a score of 76.50 with a fairly effective criterion. While the control class with an average difference of 26 obtained an N-Gain score of 0.52 on the moderate criterion and an effectiveness level of 52.35, a less effective.